HLA Alleles are Genetic Markers for Susceptibility and Resistance towards Leprosy in a Mexican Mestizo Population. (27th December 2016) - Aguilar‐Medina, Maribel; Escamilla‐Tilch, Monica; Frías‐Castro, Luis Octavio; Romero‐Quintana, Geovanni; Estrada‐García, Iris; Estrada‐Parra, Sergio; Granados, Julio; Arambula Meraz, Eliakym; Sánchez‐Schmitz, Guzman; Khader, Shabaana Abdul; Rangel‐Moreno, Javier; Ramos‐Payán, Rosalío
Summary: Despite the use of multidrug therapy, leprosy remains endemic in some countries. The association of several human leucocyte antigen (HLA) alleles and gene polymorphisms with leprosy has been demonstrated in many populations, but the major immune contributors associated to the spectrum of leprosy have not been defined yet. In this study, genotyping of HLA‐A, ‐B, ‐DR, and ‐DQ alleles was performed in leprosy patients ( n = 113) and control subjects ( n = 117) from the region with the highest incidence for the disease in México. The odds of developing leprosy and lepromatous subtype were 2.12‐ and 2.74‐fold higher in carriers of HLA‐A*28, and 2.48‐ and 4.14‐fold higher for leprosy and dimorphic subtype in carriers of DQB1*06. Interestingly, DQB1*07 was overrepresented in healthy individuals, compared to patients with leprosy (OR = 0.08) and the lepromatous subtype (OR = 0.06). These results suggest that HLA‐A*28 is a marker for predisposition to leprosy and the lepromatous subtype and DQB1*06 to leprosy and the dimorphic subtype, while DQB1*07 might be a resistance marker in this Mestizo population.